2019
DOI: 10.1021/acsomega.9b00454
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ferromagnetic Sr3YCo4O10+δ and Carbon Black-Reinforced Polyvinylidenefluoride Composites toward High-Performance Electromagnetic Interference Shielding

Abstract: In this study, we fabricated composites of conducting carbon black (CB), room-temperature ferromagnetic Sr 3 YCo 4 O 10+δ (SYCO) and polyvinylidenefluoride (PVDF) by the solution mixing and coagulation method for the first time. During the nucleation process of PVDF, the presence of SYCO and CB individually facilitates the crystallization of polar β and semipolar γ phases along with the nonpolar α phase in PVDF. The dc electrical conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 69 publications
(117 reference statements)
0
32
0
Order By: Relevance
“…And absorption loss comes from ohmic and heat loss in the shielding material. [ 48 ] SE M is neglected when SE T is over 15 dB. [ 49 ]…”
Section: Resultsmentioning
confidence: 99%
“…And absorption loss comes from ohmic and heat loss in the shielding material. [ 48 ] SE M is neglected when SE T is over 15 dB. [ 49 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, with a further increase in the CBNPs loading (Figure 3(e, f)), the peak intensity at 2θ = 20.2° gradually decreases with a gradual increase in the intensity of other peaks. For PVDF/CBNPs nanocomposite (90/10) (Figure 3(g)), the relative intensity of the PVDF peak at 2θ = 20.2° shows a gradual decrease while the characteristic peaks at 2θ = 44.3° and 2θ = 64.2° displays a gradual increase indicating the effective reinforcement of CBNPs into the PVDF matrix 42 . The variations in the intensity of XRD peaks show that the addition of nanofillers has strongly influenced the crystallinity of the polymeric chains.…”
Section: Resultsmentioning
confidence: 99%
“…For PVDF/ CBNPs nanocomposite (90/10) (Figure 3(g)), the relative intensity of the PVDF peak at 2θ = 20.2 shows a gradual decrease while the characteristic peaks at 2θ = 44.3 and 2θ = 64.2 displays a gradual increase indicating the effective reinforcement of CBNPs into the PVDF matrix. 42 The variations in the intensity of XRD peaks show that the addition of nanofillers has strongly influenced the crystallinity of the polymeric chains. Therefore, the crystallite sizes were evaluated using the Scherer formula for all the nanocomposite films and results are depicted in Table 2.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…Novel composites consisting of polyvinylidene fluoride, conductive carbon black and ferromagnetic Sr 3 YCo 4 O 10+ δ (SYCO), prepared by the solution blending and coagulation method, were deeply studied for the first time in the work. 273 It was revealed that during the nucleation process of PVDF, CB and SYCO facilitated the crystallization of semipolar γ and polar β phases, as well as the nonpolar α phase in PVDF matrix. The electrical dc conductivity of PVDF significantly increased from 1.54 × 10 −8 to 9.97 S m −1 with application of 30 wt% CB, and it was almost constant with respect to the content of SYCO.…”
Section: Materials Used For Emi Shieldingmentioning
confidence: 99%
“…Novel composites consisting of polyvinylidenefluoride, conductive carbon black and ferromagnetic Sr 3 YCo 4 O 10+δ (SYCO), prepared by the solution blending and coagulation method, were for the first time deeply studied in the work [273]. It was revealed that during respectively.…”
Section: Hybrid Composites Based On Carbon Based Fillers and Magneticmentioning
confidence: 99%